The Relationship of the Intensity of Balance Bike Activities on the Emotional Resilience of Children Aged 5-6 Years in Malang - Anggraini, Dinda Putri; Putra, Yudithia Dian; Maningtyas, Rosyi Damayani Twinsari; Pramono, Pramono (Universitas Negeri Malang, 2024)
This research aims to determine the relationship between the intensity of balance bike activities and the emotional resilience of children aged 5-6 years in Malang. This research was conducted on 35 children aged 5-6 years at the XBC Pushbike Malang, FF Reborn Pushbike Malang and CAKids Pushbike Malang clubs. The type of research used in this research is quantitative descriptive research with correlation and determination test analysis methods. The sampling technique used was purposive sampling. The data collection technique in this research was using a questionnaire which was distributed to the children's parents. The results of research using the Pearson product moment correlation statistical test show that the Sig (2-tailed) value is 0.009 with a correlation coefficient value of 0.437 and a determination value of 0.191. The results show that there is a significant relationship and influence between the intensity of balance bike activities on emotional resilience, with a sufficient or moderate level of relationship strength and a positive relationship direction.